Successful Expulsion of a Golf Ball from the Sigmoid Colon Using Volume Laxatives. (6th January 2023) - Grantham, James P.; Hii, Amanda; Bright, Tim; Liu, David
Abstract : Background . Rectal foreign bodies form a surprisingly frequent cause of presentation to the emergency department. The materials inserted constitute a wide range of size, shape, and texture with each presenting a unique set of challenges. Despite a seemingly innocuous presentation, if not recognised early and managed accordingly, significant complications can develop including obstruction, perforation, and sphincteric injury. The existing doctrines advocate endoscopic intervention after simple measures fail and advise against the use of laxative therapy due to concerns for complications that may arise. The authors of this study challenge this notion, provided certain conditions are met. Case Presentation . We report the case of a 14-year-old boy who inserted a golf ball into his rectum, which subsequently migrated proximally into the sigmoid colon on plain radiographic films. The patient was asymptomatic on presentation, and there was no clinical evidence of bowel injury or mechanical bowel obstruction. Endoscopic removal of the golf ball was pursued under general anaesthesia. Despite protracted efforts, the golf ball was not able to be retrieved endoscopically. In an attempt to avoid aggressive surgery, volume laxatives were administered with successful passage of the golf ball several hours later. Conclusions . This case discusses the unique technical challenges, which may be encountered when attempting to retrieve a large, spherical, and non-confirming foreign body entrapped above the rectosigmoid junction and how these factors can complicate endoscopic retrieval. The authors advocate that in the absence of a mechanical bowel obstruction, patients with foreign bodies possessing physical properties that are amenable to spontaneous passage, a trial of strong aperients, should be considered first line. The author's contention is that direct escalation to removal of foreign body in theatre can be resource draining and may expose the patient to additional risk.